Pengaruh Kelengkapan Produk, Harga dan Kualitas Layanan Terhadap Loyalitas Pelanggan Pada Dina Swalayan Pace Nganjuk : Cv. Anugerah Maju Sejahtera - Fika Arum Septiana; Erwin Syahputra; Rike Kusuma Wardhani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine partially and simultaneously the independent variables Product Completeness, Price and Service Quality on the dependent variable customer loyalty at Dina Swalayan (Cv. Anugerah Maju Sejahtera) Plosoharjo Pace Nganjuk. The type of research used is quantitative research with a survey method which is carried out to find numerical data as a medium for processing research data using statistical tests. The research population is all customers who have made purchases with a total population over three months, namely an estimated 870 customers. The sampling technique used was the Non Probability sampling method with a sample size of 90 respondents. The data sources for this research are primary data and secondary data by taking questionnaires directly to customers. The methods used in carrying out the analysis are validity, reliability, classical assumptions, multiple regression, T test, F test, coefficient of determination R2. The results of the research show: There is a partial influence of product completeness (X1) on customer loyalty (Y) by showing that the t test results obtained a Sig value. 0.000 < 0.005 then H0 is rejected and Ha is accepted. The partial influence of price (X2) on customer loyalty (Y) by showing the results of the t test obtained a Sig value. 0.000 < 0.05 then H0 is rejected and Ha is accepted. The partial influence of service quality (X3) on customer loyalty (Y) shows that the t test results obtained a Sig value. 0.000 < 0.05 then H0 is rejected and Ha is accepted. The simultaneous influence of product completeness (X1), price (X2), and service quality (X3) on customer loyalty by showing the F test results obtained a Sig value. 0.000 < 0.05.